2000
DOI: 10.1161/01.hyp.35.1.307
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 and Cyclooxygenase Metabolites Contribute to the Endothelin-1 Afferent Arteriolar Vasoconstrictor and Calcium Responses

Abstract: Abstract-Arachidonic acid metabolites contribute to the endothelin-1 (ET-1)-induced decrease in renal blood flow, but the vascular sites of action are unknown. Experiments performed in vitro used the rat juxtamedullary nephron preparation combined with videomicroscopy. The response of afferent arterioles to ET-1 was determined before and after cytochrome P450 (CYP450) or cyclooxygenase (COX) inhibition. Afferent arteriolar diameter averaged 20Ϯ1 m (nϭ17) at a renal perfusion pressure of 100 mm Hg. Superfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 32 publications
12
78
2
Order By: Relevance
“…Along these lines, Oyekan and McGiff (28) demonstrated that the endothelin-1-evoked decreases in renal blood flow and glomerular filtration were enhanced by COX inhibition. In contrast, indomethacin attenuated the increase in renal vascular resistance, the afferent arteriolar decrease in diameter, and renal microvascular smooth muscle cell calcium response to endothelin-1 (18,27). The results of the present study also suggest involvement of COXderived vasodilator and vasoconstrictor metabolites in the afferent arteriolar response to endothelin-1.…”
Section: Discussionsupporting
confidence: 43%
“…Along these lines, Oyekan and McGiff (28) demonstrated that the endothelin-1-evoked decreases in renal blood flow and glomerular filtration were enhanced by COX inhibition. In contrast, indomethacin attenuated the increase in renal vascular resistance, the afferent arteriolar decrease in diameter, and renal microvascular smooth muscle cell calcium response to endothelin-1 (18,27). The results of the present study also suggest involvement of COXderived vasodilator and vasoconstrictor metabolites in the afferent arteriolar response to endothelin-1.…”
Section: Discussionsupporting
confidence: 43%
“…However, these results are confounded because heme oxygenase inducers also stimulate the formation of the vasodilatory gas carbon monoxide and may influence nitric oxide synthase activity and produce vasodilatory factors via the cGMP pathway (35). Dibromo-olefinic fatty acids are relatively specific inhibitors of arachidonic acid -/( -1)-hydroxylation and have been extensively used to characterize 20-HETE biological effects in vitro and in situ (17,21,46,54). The most potent inhibitor of arachidonic acid -hydroxylation to date is N-hydroxy-NЈ-(4-butyl-2-methylphenyl)-formamidine (HET-0016) (33).…”
Section: Discussionmentioning
confidence: 99%
“…(23). Endothelin-1 (ET-1) also stimulates the formation of 20-HETE and 20-HETE contributes to the renal vasoconstrictor response to this agonist as well (21,22). Thus, the present study examined that the changes in urinary excretion of 20-HETE and immunohistochemistry of CYP4A protein in kidneys from rats with CsA-induced nephrotoxicity because elevations in renal ANG II (29 -31) and ET-1 levels (24, 31) have been implicated in mediating the decline in renal function in this model.…”
Section: Effect Of Csa On the Renal Expression Of Cyp4a Proteinmentioning
confidence: 99%
“…20-HETE is also a potent constrictor of renal arterioles in rats (17,18) and dogs (19) and the vasoconstrictor response to 20-HETE is mediated by the blockade of large conductance Ca 2+ -activated K + -channels (19,20). Recent studies have also indicated that the production of 20-HETE is stimulated by ET-1 (21,22) and ANG II (23 -25) and that the elevation in the levels of 20-HETE in vascular smooth muscle cells potentiates the response to these vaso-constrictors in the renal vasculature. There is one report that CsA increases the expression of CYP4A enzymes and the omega-hydroxylation of fatty acids in the kidney of rats (26).…”
Section: Introductionmentioning
confidence: 99%